Jazz - Tanner, Paul 1917-2013; Megill, David W. (New York, NY McGraw Hill LLC, 2024)
This new edition of Jazz is to offer students a listening-based approach to the evolutionary development of America's unique art form"--
includes index.
ges 18+
description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Jazz -- History and criticism